The practice of performance-based contracting in developing countries' public procurement: the case of ethiopia. Issue 3 (1st April 2017) - Ambaw, Baynesagn Asfaw; Telgen, Jan
Abstract : Performance-Based Contracting (PBC) is widely accepted as a useful tool. It is believed that the use of PBC can assist the efficient utilization of the public resources. The objective of this research is to assess the extent of PBC application and the obstacles to applying it in the public procurement systems of developing countries. Interviews and factual analysis of procurement guidelines and contracts are used to collect data for this research. The analysis results indicate that the majority of public organizations have not yet used PBC even though it is allowed by the law. This is due partly to lack of clarity in the procurement laws and lack of capacity to use PBC.